2015
DOI: 10.1007/s10875-015-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the human tetraspanin CD81 gene is expressed as a truncated protein but does not enable CD19 maturation and cell surface expression

Abstract: A homozygous mutation in a splice site of the CD81 gene was identified previously in a patient, as the cause in a case of common variable immune deficiency (CVID). CD19 expression is reduced in mice that lack CD81; however, B cells in this patient lacked completely CD19 surface expression. The mutation led to an absence of the CD81 protein on the cell surface and it was assumed that the CD81 protein was not produced. Here we demonstrate that a truncated human CD81 mutant (CD81mut) was actually produced, but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
(50 reference statements)
1
19
0
Order By: Relevance
“…However, the CD19 protein is produced in the absence of CD81, but is retained intracellularly as previously demonstrated (10). As expected, CD19WT and all the mutated CD19 proteins were produced in CD81 POS cells as evident by western blot analysis (Figure 2, left panel).…”
Section: Mutations Of the Motif's Arginines And Lysines Affect The Glsupporting
confidence: 84%
See 1 more Smart Citation
“…However, the CD19 protein is produced in the absence of CD81, but is retained intracellularly as previously demonstrated (10). As expected, CD19WT and all the mutated CD19 proteins were produced in CD81 POS cells as evident by western blot analysis (Figure 2, left panel).…”
Section: Mutations Of the Motif's Arginines And Lysines Affect The Glsupporting
confidence: 84%
“…Recent studies have shown that a subgroup of this family, known as TspanC8 (Tspan5, 10,12,14,15,17,33), promotes ER exit and surface expression of ADAM10 (a disintegrin and metalloprotease 10) (12)(13)(14). This led to the suggestion that these tetraspanins mask an arginine-lysine rich motif in the intracellular domain of ADAM10 (15) thereby enabling ADAM-10 surface expression.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have highlighted the importance of CD81 in CD19 export to the cell surface, and a CD81 truncation in a human patient results in a combined variable immunodeficiency phenotype and intracellular retention of CD19 in cell-based assays (van Zelm et al, 2010; Vences-Catalan et al, 2015). Here, we used a flow cytometry assay to measure the amount of CD19 at the surface of transfected cells, and the ability of CD81 to increase the amount of CD19 detected at the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…CD81 is also among the most well characterized tetraspanins because of its essential role in B-cell biology (Cherukuri et al, 2004b; Mattila et al, 2013), forming a multi-protein complex with CD19, CD21/CR2, and CD225 to regulate B cell receptor function. The importance of CD81 in B cell function is further highlighted by the recent report of a common variable immunodeficiency patient who has a germ line mutation that produces an alternatively spliced, truncated form of CD81 (van Zelm et al, 2010), which appears to sequester CD19 intracellularly (Vences-Catalan et al, 2015). CD81 is also a host factor that interacts with the Hepatitis C virus E2 envelope protein and is required for efficient HCV entry (Bradbury et al, 1992; Pileri et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, this CD81 mutation was assumed to completely abolish CD81 protein expression 39. However, it was recently demonstrated that in fact a truncated CD81 protein was produced 47. Both the mutant CD81 and the normal CD19 protein were retained intracellularly, resulting in absent CD81 and CD19 surface expression 47…”
Section: Genes Associated With Monogenic Forms Of Cvidmentioning
confidence: 99%